In Two Minds: Similarity, Threat, and Prejudice Contribute to Worse Mindreading of Outgroups Compared With an Ingroup. (January 2020) - Ekerim-Akbulut, Müge; Selçuk, Bilge; Slaughter, Virginia; Hunter, John A.; Ruffman, Ted
We examined Turkish participants' mindreading accuracy toward ingroup versus outgroup targets. Three hundred and fifty-four Turkish participants were randomly assigned to one of three target groups: Turkish, Syrian, or Norwegian. The mindreading accuracy for these targets was measured along with the perceived cultural similarity of the target to the ingroup, as well as prejudice and threat perception. Participants evidenced higher mindreading accuracy toward Turkish targets compared with Syrian and Norwegian targets. Mindreading accuracy for the Syrian and Norwegian targets did not differ, but lower perceived similarity to the Turkish ingroup significantly predicted lower mentalizing for Syrian and Norwegians. In the Syrian target group, lower perceived similarity interacted with lower education and higher prejudice, resulting in a further reduction in mindreading. For Norwegian targets, lower similarity impaired mindreading through an interaction with higher threat perception. Results indicate that even when mentalizing capacity is mature, intergroup factors are linked with the deployment of mindreading.